Production Fruitière De Quatre Essences Ligneuses Dans La Forêt De Nassou En Zone Soudanienne Du Bénin - Pierre, Agbani Onodjè; Kisito, Gandji; Frédéric, Tovissodé; Hahn, Karen; Brice, Sinsin (European Scientific Journal, ESJ, 2017)
Rural populations are closely dependent on plant resources for their daily needs. Fruit productivity of these species is an indicator of their economic potential and their capacity to regenerate. This is also fundamental to define sustainable management strategies of species. The present study assessed the fruits and seeds productivity of four forest species such as Vitex doniana, Afraegle paniculata, Diospyros mespiliformis and Kigelia africana according to the diameter class of trees. The study was carried out in the Nassou forest in soudanian zone of Benin. 09 to 90 trees belonging to four diameter classes (10-20 cm, 20-30 cm, 30-40 cm, and≥ 40 cm) were sampled for each species. The method used is the counting of fruits fallen under the tree through a periodic collection carried out every five days from the fructification to the end of the cycle and the fall of the last fruit. Seeds were then extracted from fruits. Generalized linear models of Poisson family were used to analyse data. Results revealed that the diameter class on the one hand influence significantly (Prob. ≤ 0.01) the production of fruits of K. africana and V. doniana, and on the other hand the production of seeds of A. paniculata, D. mespiliformis and V. doniana. Overall, fruits and seeds production is higher for the biggest tress (≥ 40 cm). Therefore, the diameter of the four studied species would be very useful for genetic improvement aiming the increasing of their productivity.